Body measurement system for making clothing pattern / Nurul Shukriah Ariffin - Ariffin, Nurul Shukriah (2013)
This thesis deals with the development o f body measurement system for making clothing pattern. Body measurement system for making clothing pattern was developed to measure upper body parts which are shoulder width, body length, chest circumference and short sleeve to produce a clothing pattern for short sleeve round neck t-shirt. The objectives of the research are to identify parts o f the human upper body should be measured to get upper body measurement and to develop a system to determine the body measurement for making clothing pattern using image processing. This research presents a method based on image processing which can extract the measurements of upper body based on reference point and distance measurement in MATLAB. Image processing using MATLAB is chosen because it can generate high speed result compare to another programming language. Graphical User Interface (GUI) in MATLAB library is been used to create the interface o f the system. In this research, 50 image o f primary student from Sekolah Kebangsaan Mohd Ariff Abdullah is used to get the measurement result. A few step need to follow in order to get the result. There are image preprocessing, image threshold and edge detection. The experiment results show that the lower of percentage accuracy system performance is still in the range o f percentage limit which is 94%. As a conclusion, the new system has been developed and the measuring system using image processing in MATLAB can be applied in body measurement. This will enhanced the system in getting precise and accurate measurement and can be used anytime and anywhere.